Satellite Internet：Application and Development - SHAN Chao; MA Shaoxuan; GU Xin; WANG Niwei (天地一体化信息网络)
This paper explored the composition and implementation forms of satellite Internet, building upon an evaluation of the limitations of current terrestrial internet. It provided a comprehensive analysis of various application scenarios of satellite Internet in aerospace, aviation, maritime, and terrestrial domains. Subsequently, the challenges faced by satellite Internet, included issues of frequency congestion, latency, high launch and maintenance costs, were discussed, along with proposed corresponding measures to address these challenges. Finally, the future development of satellite internet were predicted.